An Alternative Instructional Model: Teaching Medical Translation Online - Asuncion Gómez, María; Weinreb, Steven (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2002)
AbstractTeaching medical translation has traditionally been performed in classrooms with limited use of technical advances. We report our experiences in the teaching of this translation specialty via the use of the Internet within the context of a university-based translation and interpretation program. The teaching model and course structure are presented along with our suggestions for the role of distance learning in the educational process for modern translators.